Preservice Special Education Teachers’ Perceptions of Field Experience with English-Language Learner Students - David L. Adams; Casey Hord (Education Sciences, 2023)
In the United States, students are increasingly diverse in their academic and linguistic abilities. The specialization of teaching professionals has been the primary method used in order to respond to this increase. Programs for these professionals have largely been siloed along the dichotomous groupings of students identified in law, namely, disabled/nondisabled or English proficient/nonproficient. However, the reality of students is much more complex and interdisciplinary approaches present an opportunity for meeting the realistic needs of all students. This study used a one-time, open-ended survey to gather the perceptions of four preservice special education teachers who worked collaboratively with students identified as English-Language Learners (ELL) and their teacher. These perceptions were analyzed in light of recent literature calling for increased collaboration among professionals in special and bilingual education.